Addition of platelet concentrate to dermo-epidermal skin graft in deep burn trauma reduces scarring and need for revision surgeries - Prochazka, Vaclav; Klosova, Hana; Stetinsky, Jiri; Gumulec, Jaromir; Vitkova, Katerina; Salounova, Dana; Dvorackova, Jana; Bielnikova, Hana; Klement, Petr; Levakova, Veronika; Ocelka, Tomas; Pavliska, Lubomir; et al. (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2014)
BACKGROUND: [corrected] Deep skin burn injuries, especially those on the face, hands, feet, genitalia and perineum represent significant therapeutic challenges. Autologous dermo-epidermal skin grafts (DESG) have become standard of care for treating deep burns. Additionally, human autologous thrombin activated autologous platelet concentrate (APC) has gained acceptance in the setting of wounds. While each of these interventions has been independently shown to accelerate healing, the combination of the two has never been evaluated. We hypothesized that the addition of platelets (source of growth factors and inhibitors necessary for tissue repair) to the DESG (source of progenitor cells and of tissue proteases necessary for spatial and temporal control of growth regulators released from platelets) would create the optimal environment for the reciprocal interaction of cells within the healing tissues. METHODS: We used clinical examination (digital photography), standardised scales for evaluating pain and scarring, in combination with blood perfusion (laser Doppler imaging), as well as molecular and laboratory analyses. RESULTS: We show for the first time that the combination of APC and DESG leads to earlier relief of pain, and decreased use of analgesics, antipruritics and orthotic devices. Most importantly, this treatment is associated with earlier discharges from hospital and significant cost savings. CONCLUSIONS: Our findings indicate that DESG engraftment is facilitated by the local addition of platelets and by systemic thrombocytosis. This local interaction leads to the physiological revascularization at 1-3 months. We observed significant elevation of circulating platelets in early stages of engraftment (1-7 days), which normalized over the subsequent 7 and 90 days.
Keywords: Skin Transplantation; Female; Pain Measurement; ultrasonografie; transplantace kůže; ženské pohlaví; jizva; Wound Healing; pruritus; lidé; Pruritus; Laser-Doppler Flowmetry; Ultrasonography; měření bolesti; Cicatrix; Reoperation; bolest; plazma bohatá na destičky; reoperace; Platelet-Rich Plasma; Male; Burns; hojení ran; laser doppler flowmetrie; Pain; lidé středního věku; mužské pohlaví; popálení; Middle Aged; Humans